2010
DOI: 10.1158/1055-9965.epi-09-0917
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cytokine Gene Polymorphisms and Gastric Precancerous Lesions: Systematic Review and Meta-analysis

Abstract: Polymorphisms within interleukin-1 (IL1) and tumor necrosis factor α (TNFA) gene clusters are associated with an increased risk of gastric cancer. However, their role in gastric precancerous lesions remains poorly understood. Our objective was to perform a meta-analysis of studies addressing the association between IL1B-511, IL1RN variable number of tandem repeat, and TNFA-308 gene polymorphisms and gastric precancerous lesions, including original data from Portugal and Mozambique. Published studies on the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…In the populations of East Asia and Europe alleles of interleukin-1 beta are associated with an increased risk of atrophic gastritis and gastric cancer (El-Omar et al, 2000;Matsukura et al, 2003;Yamada et al, 2006). A meta-analysis study on the relationship of IL1B polymorphism with the development of precancerous conditions of the stomach was conducted by Peleteiro et al (Peleteiro et al, 2010). In particular, there is a weak association of the development of gastric epithelial metaplasia in carriers of T allele at position IL1B-511 (OR=1.86) (Peleteiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the populations of East Asia and Europe alleles of interleukin-1 beta are associated with an increased risk of atrophic gastritis and gastric cancer (El-Omar et al, 2000;Matsukura et al, 2003;Yamada et al, 2006). A meta-analysis study on the relationship of IL1B polymorphism with the development of precancerous conditions of the stomach was conducted by Peleteiro et al (Peleteiro et al, 2010). In particular, there is a weak association of the development of gastric epithelial metaplasia in carriers of T allele at position IL1B-511 (OR=1.86) (Peleteiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study on the relationship of IL1B polymorphism with the development of precancerous conditions of the stomach was conducted by Peleteiro et al (Peleteiro et al, 2010). In particular, there is a weak association of the development of gastric epithelial metaplasia in carriers of T allele at position IL1B-511 (OR=1.86) (Peleteiro et al, 2010). Previously, the association of IL1B-511T/-31C alleles and IL1RN*2 with the risk of gastric cancer has been shown in the European population by El-Omar et al (El-Omar et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis showed that only the IL1RN×22 Genotype seems to consistently increase the risk of gastric precancerous lesions, supporting a role for this polymorphism in the early stages of gastric carcinogenesis. 25 Therefore, it seems that the presence of C/T genotypes in the IL-1B-31 did not increase the susceptibility for the development of gastric carcinoma, especially in early stages. This discrepancy between our results and previous results will be due to small sample number and ethnic differences.…”
Section: Discussionmentioning
confidence: 89%
“…pylori infection-mediated cytokine expression is essentially involved in the development of chronic gastritis and stomach tumors. TNF-α and IL-1β are considered to be particularly important, because epidemiological studies have suggested that their polymorphisms are associated with the increased risk of gastric carcinogenesis [103][104][105]. Oshima et al recently reported that additional knockout of TNF-α or TNF-α receptor results in the significant suppression of gastric tumor development in the K19-Wnt1/C2mE mice [106].…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%